An Extremely Elongated Cloud Over Arsia Mons Volcano on Mars: I. Life Cycle. Issue 3 (9th March 2021) - Hernández‐Bernal, J.; Sánchez‐Lavega, A.; del Río‐Gaztelurrutia, T.; Ravanis, E.; Cardesín‐Moinelo, A.; Connour, K.; Tirsch, D.; Ordóñez‐Etxeberria, I.; Gondet, B.; Wood, S.; Titov, D.; Schneider, N. M.; et al.
Abstract: We report a previously unnoticed annually repeating phenomenon consisting of the daily formation of an extremely elongated cloud extending as far as 1, 800 km westward from Arsia Mons. It takes place in the solar longitude (Ls) range of ∼220°–320°, around the Southern solstice. We study this Arsia Mons Elongated Cloud (AMEC) using images from different orbiters, including ESA Mars Express, NASA MAVEN, Viking 2, MRO, and ISRO Mars Orbiter Mission (MOM). We study the AMEC in detail in Martian year (MY) 34 in terms of local time and Ls and find that it exhibits a very rapid daily cycle: the cloud growth starts before sunrise on the western slope of the volcano, followed by a westward expansion that lasts 2.5 h with a velocity of around 170 m/s in the mesosphere (∼45 km over the areoid). The cloud formation then ceases, detaches from its formation point, and continues moving westward until it evaporates before the afternoon, when most sun‐synchronous orbiters make observations. Moreover, we comparatively study observations from different years (i.e., MYs 29–34) in search of interannual variations and find that in MY33 the cloud exhibits lower activity, while in MY34 the beginning of its formation was delayed compared with other years, most likely due to the Global Dust Storm. This phenomenon takes place in a season known for the general lack of clouds on Mars. In this paper we focus on observations, and a theoretical interpretation will be the subject of a separate paper. Plain Language Summary: In September and October 2018, the Visual Monitoring Camera onboard Mars Express observed a spectacular water ice cloud extending as far as 1, 800 km westward from the Arsia Mons Volcano on Mars. This curious extremely elongated cloud caught the attention of the public (http://www.esa.int/Science_Exploration/Space_Science/Mars_Express/Mars_Express_keeps_an_eye_on_curious_cloud ). We study this Arsia Mons Elongated Cloud (AMEC) with the aid of several instruments orbiting Mars. We find that the AMEC repeated regularly each morning for a number of months, and that it is an annually repeating phenomenon that takes place every Martian year around the Southern Hemisphere during spring and summer. The AMEC follows a rapid daily cycle: it starts to expand from Arsia Mons at dawn at an altitude of about ∼45 km, and for ∼2.5 h it expands westward as fast as 170 m/s (around 600 km/h). The cloud then detaches from Arsia Mons and evaporates before noon. In previous Martian years, few observations of this phenomenon are available because most cameras orbiting Mars are placed in orbits where they can only observe during the afternoon, whereas this cloud takes place in the early morning, when the observational coverage is much lower. Key Points: We report a new phenomenon consisting of an extremely elongated water ice cloud (up to 1, 800 km) extending westward from the Arsia Mons volcano The cloud reaches the mesosphere (45 km), and expands at a velocity of around 170 m/s in Martian Year 34. This cloud repeatedly forms in the early mornings, and repeats in a daily cycle between Ls 220° and 320° every Martian year